2007
DOI: 10.1111/j.1460-9568.2006.05257.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+/K+ ATPase potentiates synaptic transmission in tactile sensory neurons of the leech

Abstract: Increasing evidence indicates that modulation of Na(+)/K(+) ATPase activity is involved in forms of neuronal and synaptic plasticity. In tactile (T) neurons of the leech Hirudo medicinalis, Na(+)/K(+) ATPase is the main determinant of the afterhyperpolarization (AHP), which characterizes the firing of these mechanosensory neurons. Previously, it has been reported that cAMP (3',5'-cyclic adenosine monophosphate), which mediates the effects of serotonin (5HT) in some forms of learning in the leech, negatively mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…This function of FXYD2 provides a considerable scope for regulation of the membrane potential by changing the number of this γ subunit in the NKA complex or by altering the biochemical properties or protein conformation of FXYD2. Previous studies have shown that a relatively small change in the membrane potential by modulating the NKA activity can markedly affect the synaptic transmission [33]. We found that loss of FXYD2 increased the number of small DRG neurons with a low frequency of AP firing, and it reduced the sEPSC frequency in the dorsal spinal cord.…”
Section: Fxyd2 Regulates the Neuronal Membrane Potential And Synapticsupporting
confidence: 46%
“…This function of FXYD2 provides a considerable scope for regulation of the membrane potential by changing the number of this γ subunit in the NKA complex or by altering the biochemical properties or protein conformation of FXYD2. Previous studies have shown that a relatively small change in the membrane potential by modulating the NKA activity can markedly affect the synaptic transmission [33]. We found that loss of FXYD2 increased the number of small DRG neurons with a low frequency of AP firing, and it reduced the sEPSC frequency in the dorsal spinal cord.…”
Section: Fxyd2 Regulates the Neuronal Membrane Potential And Synapticsupporting
confidence: 46%
“…We show that the STS effect is due to the Na + /K + pump (Figure 3). It has been proposed for many axons that slow hyperpolarization and slowing of conduction is caused by this pump, which is activated by the massive Na + influx during repetitive spiking and causes a net deficit of positive charge (Van Essen, 1973; Gordon et al, 1990; Bostock and Bergmans, 1994; Robert and Jirounek, 1994; Vagg et al, 1998; Baker, 2000; Kiernan et al, 2004; Moldovan and Krarup, 2006; Scuri et al, 2007). Direct experimental evidence of the involvement of the pump in activity-dependent dynamics for the PD axon is missing because of the difficulty that pharmacological block of the pump also interferes with its overall role in maintaining a functional membrane potential (Ballo and Bucher, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Relevantly, a mutation in the Na + /K + pump causes rapid-onset dystonia-parkinsonism (RDP), which has symptoms to indicate that it is a pathology of cerebellar computation (Cannon, 2004; de Carvalho et al, 2004). Indeed, there is a growing body of work showing that Na + /K + pumps might subserve information processing roles in neurons (Arganda et al, 2007; Scuri et al, 2007; Forrest, 2008; Forrest et al, 2009, 2012; Pulver and Griffith, 2010; Zhang and Sillar, 2012). For cerebellar Purkinje cells, we speculate that the Na + /K + pump is not simply a homeostatic mechanism to ionic gradients; we venture that it is a computational element.…”
Section: Discussionmentioning
confidence: 99%